(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The rising numbers of missed appointments, needless and unwarranted waste of patient’s appointment time have caused an impending problem for the healthcare institutions as well as the patients. Hence it is desirable to intercede the healthcare system so as to provide smooth, uninterrupted, and sustained care for the patients. The traditional appointment booking requires hard and tedious work to get a doctor’s appointment. This paper is a case study of Quick-o-Book an online system of booking doctors’ appointments in North-East India. It also discusses the products and services offered by Quick-o-Book. The system was developed by Biswajit Paul, an entrepreneur from Silchar. Quick-o-Book provides the platform to facilitate the booking and management of patients’ appointment bookings. It also provides the healthcare workers an easy access and approaches towards managing patients’ appointments and generating relevant reports. This case is a good example of how entrepreneurs create new ventures in an attempt to find solutions to the existing social problems. It gives the readers an idea of the entrepreneurial competencies and skills needed to overcome existing problems. It tells the readers how problems are resolved by investigating and observing the current phenomenon. In the area of medical appointment booking systems at health centres, the case delves into the various decisive factors to be considered while developing an appointment booking system